Bahasa Inggris - Intan Nia Selvia; Astri Wahyu Ningsih; Bachrudin Syahroni; M Yudi Mahadianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research examines how work-life balance and burnout influence the performance of workers from Generation Z. A quantitative research methodology was employed, particularly through a survey technique. Data was gathered using questionnaires sent to Generation Z employees across different sectors. The findings reveal that a positive work-life balance enhances employee performance, whereas burnout significantly detracts from it. Consequently, companies should establish policies that promote work-life balance and develop strategies to alleviate burnout, thus enhancing employee productivity and overall well-being.